Indicadores SPA para avaliação da performance - Alves, Diana (2022)
In recent years we have witnessed a significant increase in the number of spas inside and outside hotel units. Hotels are facing a complementary activity to the traditional services of accommodation and food and beverages which represents a determining and differentiating factor for the demand. On the other hand, there is a need to develop tools to support decision making in order to develop good management practices in order to achieve positive results and to survive in an increasingly dynamic and globalized economic environment. In terms of management accounting, the Uniform System of Financial Reporting for spas (USFRS) represents the first uniform accounting system applied to the economic activity of the spas. This system allows the development of ratios and statistics to analyse companies and their comparability The objective of this article is the elaboration of an exploratory study in order to ascertain the existing tools at the level of literature in the support to the management of the spas, namely the adaptation of the USFRS and the operational ratios. In order to ascertain the truth of the facts, the study of a single case for convenience was used for the elaboration of a tableau de bord where relevant indicators are referenced for the evaluation of the performance of the spas. For a spa to be financially successful it is extremely important to have a management control with the use of various pilot instruments such as tableau de bord. Revenue per guest, revenue per treatment and revenue per square foot are operational ratios that should form part of the management control of a spa.